Targeting Histone Acetylation: Readers and Writers in Leukemia and Cancer. Issue 5 (September 2017) - Benton, Christopher B.; Fiskus, Warren; Bhalla, Kapil N.
Abstract : Abstract: Chromatin packaging of DNA provides a framework for transcriptional regulation. Modifications to DNA and histone proteins in nucleosomes lead to conformational changes, alterations in the recruitment of transcriptional complexes, and ultimately modulation of gene expression. We provide a focused review of control mechanisms that help modulate the activation and deactivation of gene transcription specifically through histone acetylation writers and readers in cancer. The chemistry of these modifications is subject to clinically actionable targeting, including state-of-the-art strategies to inhibit basic oncogenic mechanisms related to histone acetylation. Although discussed in the context of acute leukemia, the concepts of acetylation writers and readers are not cell-type-specific and are generalizable to other cancers. We review the challenges and resistance mechanisms encountered to date in the development of such therapeutics and postulate how such challenges may be overcome. Because these fundamental cellular mechanisms are dysregulated in cancer biology, continued research and in-depth understanding of histone acetylation reading and writing are desired to further define optimal therapeutic strategies to affect gene activity to target cancer effectively.